Flavonoids from green tea reverse insulin resistance and inflammation: in vitro and in vivo evidence - Hassan Ali, Noor; Fadhil Abbas, Nabaa; Mohamed Abbas, Zainab (Pharmakeftiki, 2025)
Flavonoids are a class of polyphenolic compounds that can be isolated from green tea (Camellia sinensis). This study has investigated the in vitro and in vivo effects of green tea flavonoids on insulin resistance and inflammation. Flavonoids were extracted from green tea using ethanol extraction followed by purification through the employment of HPLC. In vitro experiments were conducted on two cell lines in order to assess glucose uptake and inflammatory marker expression, while in vivo studies involved streptozotocin-induced diabetic mice treated with green tea-derived flavonoids (240 mg/kg) for 30 days, and with their blood glucose and glycated haemoglobin (HbA1c) levels being analysed. Our results revealed that the flavonoid treatment could significantly increase glucose uptake in vitro (p<0.05), while diabetic mice exhibited lower fasting blood glucose (p<0.001) and HbA1c (p<0.01) levels compared to untreated controls. In conclusion, these findings suggest that flavonoids may serve as effective adjunct therapies for diabetes and inflammation.